Polythiophene conductive polymer derivatives containing sulfonic ethylene oxide side chains, manufacturing method thereof, and organic light-emitting diodes and organic solar cells containing the same
Patent Information
- Application Number
- KR1020260053782
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2026-03-25
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-03-25
Smart Images

Figure 112026036278839-PAT00041_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a novel polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain introduced therein, a method for manufacturing the same, and an organic electroluminescent device and an organic solar cell containing the same. More specifically, the invention relates to a phosphorescent-sensitive organic electroluminescent device in which the novel polythiophene-based conductive polymer derivative is included in a hole injection layer and exhibits excellent luminescence characteristics of a super-fluorescent deep blue color, and an organic solar cell in which the novel polythiophene-based conductive polymer derivative is included in a hole transport layer and exhibits excellent power conversion efficiency. Background Technology
[0003] Organic light-emitting diodes (OLEDs) are displays that utilize self-luminous organic materials. This technology leverages the phenomenon where, when an electric field is applied to the organic material, the energy lost as electrons within the material transition from an excited state to a ground state is emitted in the form of light. OLEDs are classified into phosphorescence OLEDs and fluorescence OLEDs.
[0004] Fluorescent OLEDs are an inefficient method that utilizes only singlet excitons, which account for 25% of the light emission energy, to emit light. Therefore, phosphorescent OLEDs were developed for more efficient light emission. However, blue OLEDs have a larger difference between the electron excited state and the ground state compared to red or green OLEDs, so organic molecules capable of realizing this energy difference are limited, and even if realized, they have low efficiency, making practical application difficult.
[0005] The core light-emitting layer of an OLED mainly uses a host-dopant structure in which an impurity (dopant) capable of increasing device efficiency and color purity is added to an organic molecule (host). As a technology to improve the above-mentioned problems, a technology has been developed to form a complex compound using an auxiliary ligand and use it as a blue phosphorescent dopant, and a patent application has been filed as described in Patent Document 1.
[0006] Recently, interest in Thermally Activated Delayed Fluorescence (TADF) OLEDs and Hyperfluorescence OLEDs, which are referred to as next-generation OLEDs, has been growing.
[0007] Since OLEDs emit light using organic materials, their lifespan decreases over time due to the degradation of these materials, leading to the phenomenon of color change. This phenomenon primarily occurs in images using blue light, which has the lowest efficiency among red (R), green (G), and blue (B); the reason blue has the lowest lifespan and efficiency is the use of fluorescent materials.
[0009] Meanwhile, as solar cells attracting attention as a future eco-friendly energy source, organic solar cells with flexible characteristics are gaining prominence as a replacement for conventional inorganic semiconductor devices, whose application range is limited due to their planar structure resulting from stiffness characteristics.
[0010] Organic solar cells utilize conductive polymers to achieve the characteristics described above, enabling low-cost solution-based processes and the fabrication of large-area solar cells, along with properties such as lightness, flexibility, and low weight; however, there is also the issue of needing to improve power conversion efficiency (PCE) as an important characteristic.
[0011] Two factors determining the power conversion efficiency of organic solar cells are the materials forming the hole transport layer and the active layer, and significant research is being conducted on materials for a more efficient hole transport layer, and as an example, a developed technology has been patented as described in Patent Document 2.
[0013] Furthermore, carbon nanotubes, graphene, or MXene, which are applied as conductive materials to improve the performance of silicon anode materials in secondary batteries, have limitations in that their performance is inferior to that of existing metal-based conductive materials due to low adhesion, binding strength, and compatibility.
[0014] Accordingly, there is an urgent need to develop a new material capable of performing multiple functions, such as being applicable to hole transport layers in organic solar cells exhibiting high power conversion efficiency, as well as being applicable to ultra-fluorescent organic light-emitting diodes (OLEDs) with superior luminescence characteristics—including deep blue brightness and external quantum efficiency—compared to existing blue phosphorescent-sensitive OLEDs, and as a conductive binder with excellent adhesion, bonding strength, and compatibility with silicon anode materials for secondary batteries. Prior art literature
[0016] Korean Registered Patent Publication No. 10-1252603 (Registered on April 3, 2013) Korean Published Patent Publication No. 10-2024-0083404 (Published on June 12, 2024) The problem to be solved
[0017] The present invention aims to provide a novel polythiophene-based conductive polymer derivative having multifunctionality and a method for manufacturing the same as a solution to the problems described above.
[0018] In addition, the present invention aims to provide a phosphorescent-sensitive organic electroluminescent device in which the polythiophene-based conductive polymer derivative is included in the hole injection layer and exhibits excellent luminescence characteristics of a superfluorescent deep blue color, and an organic solar cell in which the derivative is included in the hole transport layer and exhibits excellent power conversion efficiency.
[0019] In addition, another objective of the present invention is to provide a method for forming a thin film of a multifunctional conductive polymer derivative having excellent adhesion / bonding strength to a substrate by forming the multifunctional conductive polymer derivative as a thin film on various substrates and then using a laser beam or heat treatment. means of solving the problem
[0021] As a preferred embodiment of the present invention for achieving the above objective, the means of solving the problem is to provide a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced as represented by the following chemical formula 1.
[0022] [Chemical Formula 1]
[0023]
[0024] (wherein in the above Chemical Formula 1, R1 and R3 are each independently a straight-chain or branched-chain alkylene group having 1 to 10 carbon atoms, and R2 is an ethylene group, m is the number of repeating units of the ethylene oxide structure, which is 2, and n is the number of repeating units of the polythiophene main chain, which is an integer from 10 to 3,000. am.)
[0026] As another embodiment of the present invention, the method comprises the steps of: generating a thiophene-based sodium sulfonate salt-type precursor represented by the following formula 6 using a thiophene-based compound represented by the following formula 2; reacting the thiophene-based sodium sulfonate salt-type precursor with 1,4-butanesultone to generate a thiophene-based sodium sulfonate salt-type monomer represented by the following formula 7; polymerizing the thiophene-based sodium sulfonate salt-type monomer to generate a polythiophene-based sodium sulfonate salt-type polymer represented by the following formula 8; and sequentially performing ion exchange, dialysis, and solidification processes on the polythiophene-based sodium sulfonate salt-type polymer. Chemical formula 1a below Another means of solving the problem is to provide a method for manufacturing a novel polythiophene-based conductive polymer derivative capable of self-doping, comprising the step of producing a self-doping conductive polymer derivative represented by;
[0027] [Chemical Formula 2] [Chemical Formula 6] [Chemical Formula 7] [Chemical Formula 8] [Chemical Formula 1a]
[0028]
[0029] (However, the above Chemical formula 1a and in Chemical Formula 8, n is 10 to 3000.)
[0031] The above ion exchange is the Na of the sodium sulfonate functional group of the polythiophene-based sodium sulfonate salt-type polymer. + ul H +It can be changed to a sulfonic acid functional group through ion exchange.
[0032] The step of generating the above-mentioned self-doped conductive polymer derivative may involve sequentially performing dialysis and coagulation processes after ion exchange.
[0034] As another embodiment of the present invention, another means of solving the problem is to provide an organic electroluminescent device comprising: a first electrode; a second electrode formed opposite to the first electrode; and one or more organic layers disposed between the first electrode and the second electrode, wherein one or more of the organic layers comprises a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced as shown in Chemical Formula 1 below.
[0035] [Chemical Formula 1]
[0036]
[0037] (wherein in the above Chemical Formula 1, R1 and R3 are each independently a straight-chain or branched-chain alkylene group having 1 to 10 carbon atoms, and R2 is an ethylene group, m is the number of repeating units of the ethylene oxide structure, which is 2, and n is the number of repeating units of the polythiophene main chain, which is an integer from 10 to 3,000. am.)
[0038] The above organic layer may include one or more selected from a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer, or a mixture thereof.
[0039] The hole injection layer above may include a polythiophene-based conductive polymer derivative into which an ethylene oxide sulfonic acid side chain substituent represented by the following chemical formula 1a has been introduced.
[0040] [Chemical Formula 1a]
[0041]
[0042] (However, the above chemical formula 1 a In this case, n is 10 to 3000.
[0043] The above-mentioned light-emitting layer may be deposited by a co-deposition method of the host and the dopant.
[0044] The above organic electroluminescent device may emit a deep blue light.
[0046] As another embodiment of the present invention, another means of solving the problem is to provide an organic solar cell comprising: a first electrode; a second electrode formed opposite to the first electrode; and one or more organic layers disposed between the first electrode and the second electrode, wherein one or more of the organic layers comprise a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced as shown in Chemical Formula 1 below.
[0047] [Chemical Formula 1]
[0048]
[0049] (wherein in the above Chemical Formula 1, R1 and R3 are each independently a straight-chain or branched-chain alkylene group having 1 to 10 carbon atoms, and R2 is an ethylene group, m is the number of repeating units of the ethylene oxide structure, which is 2, and n is the number of repeating units of the polythiophene main chain, which is an integer from 10 to 3,000. am.)
[0050] The above organic layer comprises one or more selected from a hole transport layer, a photoactive layer, an electron transport layer, or a mixture thereof, and the hole transport layer may comprise a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced as shown in the following chemical formula 1a.
[0051] [Chemical Formula 1a]
[0052]
[0053] (However, the above Chemical formula 1a and in Chemical Formula 8, n is 10 to 3000.)
[0054] The above photoactive layer may be composed of a bulkhetero junction (BHJ) in which a non-fullerene electron donor and a fullerene electron acceptor are stacked in a mixed phase.
[0055] The above electron transport layer is, N,N'-Bis(N,N-Dimethylpropane-1-amine oxide)perylene-3,4,9,10-tetracarboxylic diimide It may contain (N,N'-Bis(N,N-dimethylpropan-1-amine oxide)perylene-3,4,9,10-tetracarboxylic diimide, PDINO).
[0057] As another embodiment of the present invention, a method for manufacturing an organic electronic device is provided, characterized by comprising the steps of: forming an anode on a substrate; forming an organic layer containing the compound of claim 1 on the anode; and forming a cathode on the organic layer. This is another means of solving the problem.
[0059] The above organic electronic device is an organic electroluminescent device, and the organic layer includes a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, and an electron injection layer, and the hole injection layer, the hole transport layer, the light-emitting layer, the electron transport layer, and the electron injection layer may be formed by sequentially stacking on the anode.
[0060] The hole injection layer may comprise a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced, represented by the following chemical formula 1a.
[0061] [Chemical Formula 1a]
[0062]
[0063] (However, the above Chemical formula 1a and in Chemical Formula 8, n is 10 to 3000.)
[0064] The above organic electronic device is an organic solar cell, and the organic layer includes a hole transport layer, a photoactive layer, and an electron transport layer, and the hole transport layer, the photoactive layer, and the electron transport layer may be formed by sequentially stacking on the anode.
[0065] The hole transport layer may comprise a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced, represented by the following chemical formula 1a.
[0066] [Chemical Formula 1a]
[0067]
[0068] (However, the above Chemical formula 1a and in Chemical Formula 8, n is 10 to 3000.)
[0069] As another embodiment of the present invention, the step of forming an organic layer containing the compound of claim 1 on the anode further comprises the step of irradiating a laser beam or performing heat treatment after stacking the organic layer containing the compound of claim 1 on the anode, thereby providing a method for manufacturing an organic electronic device as another means of solving the problem.
[0070] The step of forming an organic layer containing the compound of claim 1 on the anode may further include the step of irradiating a laser beam or performing heat treatment after stacking the organic layer containing the compound of claim 1 on the anode.
[0071] The step of forming an organic layer containing the compound of claim 1 on the anode may further include the step of irradiating a laser beam or performing heat treatment after depositing the organic layer containing the compound of claim 1 on the anode; and the step of developing using water as a developer. Effects of the invention
[0073] The present invention incorporates a novel polythiophene-based conductive polymer derivative into the hole injection layer of a phosphorescence-sensitive organic electroluminescent device, thereby achieving ultra-high color purity deep blue light emission with suppressed non-radiation loss and high efficiency characteristics. In particular, it has the effect of improving brightness, external quantum efficiency, current efficiency, and power efficiency.
[0074] In addition, the present invention has the effect of improving power conversion efficiency and device stability by including a novel polythiophene-based conductive polymer derivative in the hole transport layer of an organic solar cell.
[0075] Furthermore, a thin film comprising a novel polythiophene-based conductive polymer derivative according to the present invention can form a thin film capable of improving adhesion and bonding strength with various substrates through a simple coating process, rather than through complex photolithography or deposition methods. In particular, by applying the polythiophene-based conductive polymer derivative as a conductive binder for silicon anode materials in secondary batteries, it is possible to solve the problem of low adhesion and bonding strength of existing carbon-based conductive materials such as carbon nanotubes (CNT), graphene, or MXene.
[0076] The effects of the present invention are not limited to those mentioned above, and other unmentioned effects will be clearly understood by those skilled in the art from the description in the claims. Brief explanation of the drawing
[0078] FIG. 1 is a schematic cross-sectional view illustrating a multi-layer organic electroluminescent device in which a novel conductive polymer material having multifunctionality synthesized according to the present invention can be applied as a hole injection layer. Figure 2 is a graph showing the voltage-current density-luminance, EL spectrum, luminance-external quantum efficiency, and luminance-current efficiency-power efficiency results of a deep blue phosphorescent-sensitive superfluorescent organic electroluminescent device in which a novel conductive polymer material having multifunctionality is applied as a hole injection layer according to an embodiment of the present invention. FIG. 3 is a cross-sectional view illustrating a multi-layer organic solar cell in which a novel conductive polymer material having multifunctionality synthesized according to the present invention can be applied as a hole transport layer. Figure 4 shows the voltage-current density characteristics of an organic solar cell according to an embodiment of the present invention. FIG. 5 compares the adhesion / bonding strength results according to the presence or absence of heat treatment of a multifunctional conductive polymer thin film formed on a polyethylene terephthalate (PET) substrate according to an embodiment of the present invention, where FIG. 5(a) shows a substrate without heat treatment, FIG. 5(b) shows a substrate developed after without heat treatment, FIG. 5(c) shows a substrate with heat treatment, and FIG. 5(d) shows a substrate developed after heat treatment. Specific details for implementing the invention
[0079] The present invention will be described in detail below according to preferred embodiments with reference to the attached drawings, but specific descriptions of configurations and operations that are readily known to those skilled in the art will be omitted. Furthermore, it should be noted that the present invention is not necessarily limited by the following embodiments and that various modifications can be made to the invention within the scope of the technical concept of the invention.
[0080] The terms used in this specification have been selected to be as widely used as possible, taking into account their functions in the present invention; however, in specific cases, terms have been arbitrarily selected by the applicant, and in such cases, their meanings will be described in detail in the description of the invention. Accordingly, the terms used in this invention should be defined not merely by their names, but based on their meanings and the overall content of the invention.
[0082] Hereinafter, a novel polythiophene-based conductive polymer derivative having multifunctionality according to a preferred embodiment of the present invention (hereinafter referred to as the "conductive polymer derivative having multifunctionality"), a method for manufacturing the same, and an organic electroluminescent device and an organic solar cell device including the same will be described.
[0084] The present invention provides, as a preferred embodiment, a novel polythiophene-based conductive polymer derivative represented by the following chemical formula 1.
[0085] [Chemical Formula 1]
[0086]
[0087] (wherein in the above Chemical Formula 1, R1 and R3 are each independently a straight-chain or branched-chain alkylene group having 1 to 10 carbon atoms, and R2 is an ethylene group, m is the number of repeating units of the ethylene oxide structure, which is 2, and n is the number of repeating units of the polythiophene main chain, which is an integer from 10 to 3,000. am.)
[0088] As a preferred embodiment, the present invention provides a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced, represented by the following chemical formula 1a.
[0089] [Chemical Formula 1a]
[0090]
[0091] (However, in the above chemical formula 1a, n is 10 to 3000.)
[0092] The conductive polymer derivative of the above chemical formula 1a can be abbreviated as PSBE2M-EDT as Poly[4-(2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethoxy)butane-1-sulfonic acid]}.
[0094] The above compound has excellent hole injection ability and can be used as a hole injection layer composition for organic light-emitting diodes.
[0096] In addition, as another preferred embodiment, the present invention provides a method for producing a novel self-doping polythiophene-based conductive polymer derivative, comprising the steps of: producing a thiophene-based sodium sulfonate-type precursor; producing a thiophene-based sodium sulfonate-type monomer; producing a polythiophene-based sodium sulfonate-type polymer; and producing a self-doping conductive polymer derivative.
[0098] The step of producing the above-mentioned thiophene-based sodium sulfonate salt-type precursor can produce a thiophene-based sodium sulfonate salt-type precursor (compound 9) represented by the following chemical formula 6 using a thiophene-based compound (compound 5) represented by the following chemical formula 2.
[0099] [Chemical Formula 2] [Chemical Formula 6]
[0100]
[0101] The thiophene compound represented by the above chemical formula 2 can be abbreviated as compound 5, which is 2,3-Dihydrothieno[3,4-b][1,4]dioxin-2-yl)methanol.
[0102] The thiophene-based sodium sulfonate salt-type precursor represented by the above chemical formula 6 can be abbreviated as compound 9 as 2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethanol}.
[0104] Specifically, this step may include a step of generating a first intermediate (compound 7); a step of generating a second intermediate (compound 8); and a step of generating a thiophene-based sodium sulfonate salt-type precursor (compound 9).
[0106] The step of producing the first intermediate above can produce the first intermediate compound 7 represented by the following chemical formula 4 using compound 5, which is a thiophene-based compound represented by chemical formula 2, and compound 6, which is represented by chemical formula 4.
[0107] [Chemical Formula 3] [Chemical Formula 4]
[0108]
[0109] The compound represented by the above chemical formula 3 is 2-(2-chloroethoxy)ethyl p-toluenesulfonate, which can be abbreviated as compound 6.
[0110] The first intermediate represented by the above chemical formula 4 can be abbreviated as compound 7, which is 2-((2-(2-chloroethoxy)ethoxy)methyl)-2,3-dihydrothieno[3,4-b][1,4]dioxine}.
[0112] The step of generating the second intermediate (compound 8) above can generate the second intermediate compound 8 represented by the following chemical formula 5 using the first intermediate compound 7.
[0113] [Chemical Formula 5]
[0114]
[0115] The second intermediate represented by the above chemical formula 5 can be abbreviated as compound 8, 2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethyl acetate {2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethyl acetate}.
[0117] The third step of producing the above-mentioned thiophene-based sodium sulfonate salt-type precursor can produce compound 9, which is a thiophene-based sodium sulfonate salt-type precursor, using compound 8, which is the second intermediate.
[0118] [Chemical Formula 6]
[0119]
[0120] The thiophene monomer represented by the above chemical formula 6 can be abbreviated as compound 9, 2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethanol {2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethanol}.
[0122] The step of producing the above thiophene-based sodium sulfonate salt-type monomer can be performed by reacting the above thiophene-based sodium sulfonate salt-type precursor (compound 9) with 1,4-butanesultone to produce a thiophene-based sodium sulfonate salt-type monomer represented by the following chemical formula 7.
[0123] [Chemical Formula 7]
[0124]
[0125] The sodium sulfonate-type polymer compound represented by the above chemical formula 7 can be abbreviated as compound 10, which is sodium 4-(2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethoxy)butane-1-sulfonate.
[0127] The step of producing the above polythiophene-based sodium sulfonate salt-type polymer can produce a polythiophene-based sodium sulfonate salt-type polymer represented by the following chemical formula 8 by polymerizing the above thiophene-based sodium sulfonate salt-type monomer (compound 10).
[0128] In this step, the polymerization reaction can be carried out using the Konradsson method and the Okuzaki method to synthesize a conductive polymer derivative applicable to organic light-emitting diodes and organic solar cells represented by the above chemical formula 1.
[0129] Polymerization was carried out at a concentration of the monomer compound 10 in the range of 1 to 6 wt%. It was determined that conductivity was better at high concentrations of polymerization reaction, and it was determined that the conductivity of the multi-functional conducting polymer was higher when an aqueous H2SO4 solution was used as a solvent compared to when H2O was used.
[0131] According to the Konradsson method of polymerization, the above-mentioned thiophene-based sodium sulfonate-type monomer (Compound 10) is dissolved in water under a nitrogen atmosphere to prepare an aqueous solution, and separately, ferric chloride (FeCl3) and sodium persulfate (Na2S2O8) are dissolved in water to prepare an FeCl3 / Na2S2O8 aqueous solution, and then the polymerization reaction is carried out according to the method of Example 2.1 below.
[0133] And according to the Okuzaki method of polymerization, the above-mentioned thiophene-based sodium sulfonate-type monomer (Compound 10) is dissolved in water under a nitrogen atmosphere to prepare an aqueous solution, and then sulfuric acid (H2SO4) is added dropwise while cooling to room temperature. Separately, ferrous sulfate heptahydrate (FeSO4-7H2O) and ammonium persulfate ((NH3)2S2O8) are dissolved in water to prepare an aqueous solution of FeSO4-7H2O / (NH3)2S2O8, and then the polymerization reaction is carried out according to the method of Example 2.2 below.
[0135] [Chemical Formula 8]
[0136]
[0137] (However, in the above chemical formula 8, n is 10 to 3000.)
[0138] The sodium sulfonate-type polymer compound represented by the above chemical formula 8 can be abbreviated as PSBE2M-EDT-Na as poly{4-(2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethoxy)butane-1-sulfonate}.
[0140] The step of producing the above multifunctional conductive polymer derivative can produce a multifunctional conductive polymer derivative represented by Chemical Formula 1 by ion exchange, dialysis, and solidification of the above polythiophene-based sodium sulfonate salt type polymer.
[0142] In this step, the ion exchange is performed by dissolving PSBE2M-EDT-Na, a sulfonic acid sodium salt form of a multifunctional polymer, in distilled water to prepare an aqueous solution at a concentration of 1-2 wt%, and using a cation exchange resin to apply the Na₂S₂M-EDT-Na of the sodium sulfonic acid functional group of PSBE2M-EDT-Na. + ul H + An aqueous solution of PSBE2M-EDT, which is the sulfonic acid form of the self-doped polymer, is prepared by ion exchange to change it to a sulfonic acid functional group.
[0143] The above cation exchange resin is preferably Lewatit Monoplus S108H, and H-Type cation exchange resins exhibiting the same performance as Lewatit Monoplus S108H include Aldex C-800H, DuPont AmberLite FPC16UPS H, SEPLITE Monojet SC7100N H, etc. depending on the manufacturer, and can be selected and used from among the above ion exchange resins.
[0145] It is desirable to remove inorganic salts such as Na2SO4, FeSO4, and NaCl present in the solution by dialysis of the 1~2% PSBE2M-EDT aqueous solution prepared above with triple distilled water using a dialysis membrane.
[0146] It is desirable to proceed with dialysis until the yellow color of the aqueous solution (the color of Fe-related substances among inorganic salts) disappears, and for mass production, parameters such as the conductivity and pH of the aqueous solution can be set and managed.
[0147] It is desirable to perform dialysis with triple distilled water at a ratio of 7,000 to 20,000 times the actual polymer so as to sufficiently remove inorganic salts contained in the PSIBM-EDT aqueous solution.
[0148] The PSIBM-EDT aqueous solution from which inorganic salts have been removed by dialysis is concentrated to a point where it exhibits a viscosity that allows stirring, and then diluted with acetone, which is an anti-solvent, to proceed with solidification. It is preferable that the water concentration of the acetone aqueous solution be 8 to 15 wt%.
[0149] It was confirmed that the molecular weight of the solidified polymer is determined by the difference in solubility according to moisture concentration, and that there are differences in yield and conductivity.
[0150] In this step, it is preferable to perform dialysis with triple distilled water using a Spectra / Por 3 RC dialysis membrane MWCO 3.5kD.
[0152] And as another embodiment, the present invention provides an organic electroluminescent device comprising PSBE2M-EDT, a conductive polymer having multifunctionality.
[0153] For reference, FIG. 1 illustrates an organic light-emitting diode device according to Example 3 below of the present invention.
[0155] An organic electroluminescent device (100) according to the present invention comprises a first electrode (110); a second electrode (170) formed oppositely to the first electrode (110); and one or more organic layers disposed between the first electrode (110) and the second electrode (170), wherein one or more of the organic layers are as follows It is characterized by including a conductive polymer derivative having multifunctionality represented by Chemical Formula 1.
[0156] [Chemical Formula 1]
[0157]
[0158] (wherein in the above Chemical Formula 1, R1 and R3 are each independently a straight-chain or branched-chain alkylene group having 1 to 10 carbon atoms, and R2 is an ethylene group, m is the number of repeating units of the ethylene oxide structure, which is 2, and n is the number of repeating units of the polythiophene main chain, which is an integer from 10 to 3,000. am.)
[0160] The first electrode (110) is a part coated on bare glass (G) and functions as an anode, and any material having transparency and conductivity with a larger work function than the second electrode (180) described later can be used. Examples include indium tin oxide (ITO), fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), and indium zinc oxide (IZO), and preferably, ITO can be used.
[0162] The second electrode (180) is a portion formed on the second electron injection layer (170) that functions as a cathode, and can be formed opposite to the first electrode (110) and can be selected from metals. Specifically, for example, it may include one or more alloys selected from Al, Ca, Mg, and Ag, and preferably, an alloy containing LiF and Al or Al may be used sequentially coated.
[0163] Above. It is preferable to deposit LiF and aluminum in a chamber separated from the organic chamber to prevent contamination by organic matter.
[0165] The above organic layer may include one or more selected from a hole injection layer (HIL) (120), a hole transport layer (HTL) (130), an emission layer (EML) (140), a first electron transport layer (ETL) (150), a second electron transport layer (ETL) (160), an electron injection layer (EIL) (170), or a mixture thereof.
[0167] The hole injection layer (120) above may include PSBE2M-EDT, a multifunctional conductive polymer represented by the following chemical formula 1a.
[0168] [Chemical Formula 1a]
[0169]
[0170] (However, the above chemical formula 1 a In this case, n is 10 to 3000.
[0172] The hole injection layer (120) is preferably formed by UV-ozone treatment for 20 minutes on the bare glass (G) on which ITO, the first electrode (110), is deposited, to remove organic matter from the surface and make it hydrophilic, then sufficiently mixing PSBE2M-EDT, and then spin-coating at 1800~2200 rpm on the UV-ozone-treated first electrode (110) to form a film, and then heating on a hot plate at 140~160℃ for 15~25 minutes.
[0174] The hole transport layer (130) is a layer capable of stably supplying holes that have entered through the hole injection layer to the light-emitting layer, and can be placed on the hole injection layer (120). In order to allow holes to be transported and delivered smoothly, a material can be selected in which the highest occupied molecular orbital (HOMO) level of the hole transport layer (130) is deeper than the HOMO level of the light-emitting layer (140).
[0176] The hole transport layer (130) may include Poly(9-vinylcarbazole) (PVK), and a thin film may be formed by spin-coating the PVK at 1000 to 4000 rpm.
[0178] The above-mentioned light-emitting layer (140) may be a phosphorescent light-emitting layer disposed on the hole injection layer (120) or hole transport layer (130) and may consist of a host and a dopant for charge transfer.
[0179] The above host may be selected from, for example, 9-(3-(triphenylsilyl)phenyl)-9H-3,9'-bicarbazole (SiCzCz), 9,9'-(6-(3-(Triphenylsilyl)phenyl)-1,3,5-triazine-2,4-diyl)bis(9H-carbazole) (SiTrzCz2), 4,4',4"-tris(N-carbazolyl)-triphenylamine (TCTA), 1,3,5-tris(N-phenylbenzimiazole-2-yl)benzene (TPBi), 1,3-bis(9-carbazolyl)benzene (mCP), 4,4'-Bis(N-carbazolyl)-1,1'-biphenyl (CBP), 3,3-bis(carbazol-9-yl)bipheny (mCBP), or mixtures thereof, but is not limited thereto; specifically, It is more desirable to have SiCzCz or SiTrzCz2.
[0181] The above host may consist of a pair of hole-transporting hosts and electron-transporting hosts forming an exciplex, and may be selected from, for example, SiCzCz:(SiTrzCz2), TCTA:TPBi, TCTA:3TPYMB, TCTA:BmPyPB, or TCTA:BSFM, but is not limited thereto.
[0183] The above dopant may be selected from Platinum(II) 9-(4-(tert-butyl)pyridin-2-yl)-2-(3-(3-(quinolin-2-ylmethyl)-2,3-dihydro-1H-benzo[d]imidazol-1-yl)phenoxy)-9H-carbazole (Q(Bn)_Pt), N7,N7,N13,N13,5,15-hexaphenyl-9,11-bis(4-(tert-butyl)phenyl)-5,9,11,15-tetrahydro-5,9,11,15-tetraaza-19b,20b-diboradinaphtho [3,2,1-de:1',2',3'-jk]pentacene-7,13-diamine (t-Bu-v-DABNA) or mixtures thereof, but is not limited thereto.
[0185] The above-described light-emitting layer may be formed by a co-deposition method of a host and a dopant. More preferably, the light-emitting layer comprises SiCzCz:(SiTrzCz2) as a host forming an exciplex; and comprises Platinum(II) 9-(4-(tert-butyl)pyridin-2-yl)-2-(3-(3-(quinolin-2-ylmethyl)-2,3-dihydro-1H-benzo[d]imidazol-1-yl)phenoxy)-9H-carbazole(Q(Bn)_Pt), N7,N7,N13,N13,5,15-hexaphenyl-9,11-bis(4-(tert-butyl)phenyl)-5,9,11,15-tetrahydro-5,9,11,15-tetraaza-19b,20b-diboradinaphtho [3,2,1-de:1',2',3'-jk]pentacene-7,13-diamine(t-Bu-v-DABNA) as a dopant, wherein the host and the dopant are co-deposited to form It can be a single layer.
[0187] The first electron transport layer (150) may be disposed on the light-emitting layer (140) and may be composed of a material containing a chemical component that primarily attracts electrons. For this purpose, high electron mobility is required, and electrons can be stably supplied to the light-emitting layer (140) through smooth electron transport.
[0188] The first electron transport layer (150) and the second electron transport layer (160) may be selected from 2-Phenyl-4,6-bis(3-(triphenylsilyl)phenyl)-1,3,5-triazine (mSiTrz), 9,9'-(6-(3-(Triphenylsilyl)phenyl)-1,3,5-triazine-2,4-diyl)bis(9H-carbazole) (SiTrzCz2), 1,3,5-tris(N-phenylbenzimiazole-2-yl)benzene (TPBi), 1,3,5-tri(m-pyridin-3-ylphenyl)benzene (TmPyPB), 2-(4-(9,10-di(naphthalen-2-yl)anthracen-2-yl)phenyl)-1-phenyl-1H-benzo[d]imidazole (LG201) or a mixture thereof, but It is not limited to mSiTrz and TPBi, and specifically, it is more preferable.
[0190] The electron injection layer (170) may be disposed on the second electron transport layer (160) and may be formed as a single layer in which electron injection and electron transport occur simultaneously, and may use the same material as the example of the electron transport layer (150, 160), or may be selected from lithium fluoride (LiF), (8-quinolinolato)lithium (Liq), 2,6-bis(1,3,4,6,7,8-tetrahydro-2H-pyrimido[1,2-a]pyrimidin-1-yl) pyridine (Py-hpp2), or a mixture thereof, but is not limited thereto.
[0192] The bare glass (G) of the above organic electroluminescent device (100) is a substrate for coating the first electrode (110), and other usable materials may be selected from flexible and transparent materials such as quartz plates, PET (polyethyleneterephthalate), PEN (polyethylene naphthelate), PP (polyperopylene), PI (polyimide), PC (polycarbonate), PS (polystyrene), POM (polyoxyethylene), AS resin (acrylonitrile styrene copolymer), ABS resin (acrylonitrile butadienestyrene copolymer), and TAC (triacetyl cellulose), but are not limited thereto.
[0194] The thickness of each layer constituting the organic electroluminescent device according to the present invention is preferably a first electrode (ITO) / hole injection layer (PSBE2M-EDT, 45-50 nm) / hole transport layer (PVK, 15 nm) / emissive layer (EML, 50 nm) / first electron transport layer (mSiTrz, 5 nm) / second electron transport layer (TPBi, 10 nm) / electron injection layer (LiF, 1 nm) / second electrode (Al, 100 nm), but is not limited thereto.
[0195] The above organic electroluminescent device may emit a deep blue light.
[0196] According to one experimental example of the present invention, a deep blue organic electroluminescent device based on PSBE2M-EDT exhibits a deep blue color with a turn-on voltage of 6.5 V, a maximum emission peak of 468 nm, and color coordinates of (0.132, 0.126), and a maximum luminance of 6077 cd / m² 2It can be seen that the maximum external quantum efficiency, current efficiency, and power efficiency were shown to be 4%, 4 cd / A, and 1.2 lm / W, respectively, confirming that PSBE2M-EDT emits a super-fluorescent deep blue color through the use of hole injection or hole transport materials in deep blue organic electroluminescent devices and has excellent luminescence characteristics.
[0198] And as another embodiment, the present invention provides an organic solar cell comprising PSBE2M-EDT, a conductive polymer having multifunctionality.
[0199] The above organic solar cell comprises a first electrode; a second electrode formed opposite to the first electrode; and one or more organic layers disposed between the first electrode and the second electrode, wherein one or more of the organic layers may comprise a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced as represented by the following chemical formula 1.
[0200] [Chemical Formula 1] (wherein in the above Chemical Formula 1, R1 and R3 are each independently a straight-chain or branched-chain alkylene group having 1 to 10 carbon atoms, and R2 is an ethylene group, m is the number of repeating units of the ethylene oxide structure, which is 2, and n is the number of repeating units of the polythiophene main chain, which is an integer from 10 to 3,000. am.)
[0201] delete
[0202] delete
[0203] Additionally, the organic solar cell may further include a substrate as needed. That is, the first electrode may be formed on the substrate.
[0204] The above substrate may be a transparent glass substrate, or a transparent plastic substrate selected from the group consisting of polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide (PI), polycarbonate (PC), polyethersulfone (PES), polyarylate, and cycloolefin copolymer (COC) to impart flexibility.
[0205] The above organic layer comprises one or more selected from a hole transport layer, a photoactive layer, an electron transport layer, or a mixture thereof, and the hole transport layer may comprise a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced as shown in the following chemical formula 1a.
[0206] [Chemical Formula 1a]
[0207]
[0208] (However, in the above chemical formula 1a, n is 10 to 3000.)
[0209] The above photoactive layer may be composed of a bulkhetero junction (BHJ) in which a non-fullerene electron donor and a fullerene electron acceptor are stacked in a mixed phase.
[0210] The above electron transport layer is, N,N'-Bis(N,N-Dimethylpropane-1-amine oxide)perylene-3,4,9,10-tetracarboxylic diimide It may contain (N,N'-Bis(N,N-dimethylpropan-1-amine oxide)perylene-3,4,9,10-tetracarboxylic diimide, PDINO).
[0212] According to one experimental example of the present invention, an organic solar cell device based on PSBE2M-EDT can be confirmed to have a photoelectric conversion efficiency of 7.0%, with a photo-short current of 14.2 mA / cm2 and an open-circuit voltage of 0.84 V.
[0214] The present invention also provides a method for manufacturing an organic electronic device, as another embodiment, comprising the steps of: forming an anode on a substrate; forming an organic layer containing the compound of claim 1 on the anode; and forming a cathode on the organic layer.
[0215] For example, the organic electronic device is an organic electroluminescent device, and the organic layer may include a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, and an electron injection layer, and the hole injection layer, the hole transport layer, the light-emitting layer, the electron transport layer, and the electron injection layer may be formed by sequentially stacking them on the anode. In this case, the hole injection layer may include a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent represented by Chemical Formula 1a introduced therein.
[0216] For example, the organic electronic device is an organic solar cell, and the organic layer may include a hole transport layer, a photoactive layer, and an electron transport layer, and the hole transport layer, the photoactive layer, and the electron transport layer may be sequentially stacked and formed on the anode. In this case, the hole transport layer may include a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent represented by Chemical Formula 1a introduced therein.
[0218] The step of forming an organic layer containing the compound of claim 1 on the anode may further include the step of irradiating a laser beam or performing heat treatment after stacking the organic layer containing the compound of claim 1 on the anode. Alternatively, the step of forming an organic layer containing the compound of claim 1 on the anode may further include the step of irradiating a laser beam or performing heat treatment after stacking the organic layer containing the compound of claim 1 on the anode; and the step of developing using water as a developer.
[0219] The above laser beam may be irradiated in a wavelength range of 350 nm to 2 µm.
[0220] The above heat treatment may be performed on a hot plate at a temperature range of 100 to 150 degrees for 5 minutes to 2 hours.
[0223] Hereinafter, the present invention will be described in detail with reference to examples to aid in understanding. However, the following examples are merely illustrative of the content of the present invention and the scope of the present invention is not limited to the following examples.
[0225] 1. Synthesis of the self-doping conductive polymer poly[4-(2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethoxy)butane-1-sulfonic acid], PSBE2M-EDT}
[0227] <Example 1> Synthesis of Poly[4-(2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethoxy)butane-1-sulfonic acid], PSBE2M-EDT}
[0228] In Example 1, the compound PSBE2M-EDT was synthesized according to the procedure briefly illustrated in Reaction Scheme 1 below.
[0229] [Reaction Equation 1]
[0230]
[0232] <Example 1.1> Synthesis of 2-(Chloromethyl)-2,3-dihydrothieno[3,4-b]-1,4-dioxin {2-(Chloromethyl)-2,3-dihydrothieno[3,4-b]-1,4-dioxin: Compound 3}
[0233] 3,4-dimethoxythiophene (compound 1,3,4-dimethoxythiophene, 22 g, 152.6 mmol), 3-chloro-1,2-propanediol (compound 2,3-chloro-1,2-propanediol, 50.6 g, 457.8 mmol), methanesulfonic acid (2 mL, 30 mmol), and 2,6-di-tert-butyl-4-methylphenol (0.03 g, 0.1 mmol) were dissolved in a 500 mL toluene solution under a nitrogen atmosphere at 110°C o Stir at C for 24 hours.
[0234] After the reaction is finished, the reaction mixture is cooled to room temperature, and the organic reactant is extracted three times with ethyl acetate, washed with brine, and then washed again with an aqueous solution of sodium carbonate (Na2CO3). After removing the organic solvent by vacuum distillation of the organic reactant using a rotary evaporator, the product is separated by column chromatography using hexane / ethyl acetate as the developing solvent in a ratio of 10:0.5 to 10:1 (v / v), yielding a colorless compound 3 (2-(chloromethyl)-2,3-dihydrothieno[3,4-b]-1,4-dioxine (2-(chloromethyl)-2,3-dihydrothieno[3,4-b][1,4]dioxine), (22 g, 115.4 mmol)) with a yield of 76%.
[0235] Compound 3: 1 H NMR (400 MHz, CDCl3, δ (ppm)): 6.38-6.40 (q, 2H), 4.37-4.42 (m, 1H), 4.29-4.32 (dd, 1H), 4.16-4.20 (q, 1H), 3.67-3.77 (m, 2H).
[0237] <Example 1.2> Synthesis of (2,3-Dihydrothieno[3,4-b]-1,4-dioxin-2-yl)methyl acetate {(2,3-Dihydrothieno[3,4-b]-1,4-dioxin-2-yl)methyl acetate: Compound 4}
[0238] In a three-necked flask, compound 3 (2-(chloromethyl)-2,3-dihydrothieno[3,4-b][1,4]dioxine, 22 g, 115.4 mmol) synthesized in Example 1.1 and potassium acetate (45.3 g, 461.6 mmol) were dissolved in dimethyl sulfoxide (DMSO, 500 mL), and then 110 o The reaction is carried out at C for 6 hours under a nitrogen atmosphere while stirring.
[0239] After cooling the reaction mixture to room temperature, washing it three times with iced water and removing moisture with anhydrous sodium sulfate, the organic reactant is vacuum distilled using a rotary evaporator to remove the organic solvent, and then the product is separated by column chromatography using hexane / ethyl acetate as the developing solvent in a ratio of 10:1 to 10:2 (v / v), a colorless compound 4 ((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methyl acetate, 20 g, 93.35 mmol) can be obtained with a yield of 81%.
[0240] Compound 4: 1 H NMR (400 MHz, CDCl3, δ (ppm)):: 6.37-6.40 (q, 2H), 4.38-4.43 (m, 1H), 4.32-4.33 (dd, 2H), 4.23-4.27 (dd, 1H), 4.04-4.09 (m, 1H), 2.14 (s, 3H).
[0242] <Example 1.3> Synthesis of (2,3-Dihydrothieno[3,4-b][1,4]dioxin-2-yl)methanol {(2,3-Dihydrothieno[3,4-b][1,4]dioxin-2-yl)methanol: Compound 5}
[0243] Dissolve sodium hydroxide (33 g, 825 mmol) in distilled water (450 mL) in a three-necked flask. Then, add compound 4 ((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methyl acetate), (22 g, 102.7 mmol), and then 7 the reaction mixture oStirring at C for 3 hours. After cooling the reaction mixture to room temperature, the reaction product is extracted with ethyl acetate, water is removed with sodium sulfate, and the organic solvent is removed by vacuum distillation of the organic reactant using a rotary evaporator. Then, the product is separated by column chromatography using hexane / ethyl acetate as the developing solvent in a ratio of 10:2.5 (v / v), and a white solid compound 5 (2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methanol, (15 g, 87.41 mmol)) can be synthesized with a yield of 85%.
[0244] Compound 5: 1 H NMR (400 MHz, CDCl3, δ (ppm)):: 6.36-6.38 (q, 2H), 4.24-4.30 (m, 2H), 4.10-4.15 (dd, 1H), 3.84-3.94 (m, 2H).
[0246] <Example 1.4> Synthesis of 2-((2-(2-chloroethoxy)ethoxy)methyl)-2,3-dihydrothieno[3,4-b][1,4]dioxine {2-((2-(2-chloroethoxy)ethoxy)methyl)-2,3-dihydrothieno[3,4-b][1,4]dioxine : Compound 7}
[0247] Under a nitrogen atmosphere, 60% sodium hydride (NaH) (1.81 g, 30.20 mmol, 1.3 eq.) was dispersed in 30 mL of anhydrous dimethylformamide (DMF) and cooled to 0°C. HM-EDT (6.00 g, 34.84 mmol, 1 eq.) was dissolved in 12 mL of DMF to prepare an HM-EDT / DMF solution, which was added dropwise to the NaH / DMF solution over 8 minutes at 0°C. The reaction temperature was slowly raised from 0°C to room temperature and stirred for 1 hour, after which it was cooled back to 0°C. 12.63 g (40.30 mmol, 1.3 eq.) of 2-(2-chloroethoxy)ethyl p-toluene sulfonate, CE2OTs(6) was dissolved in 15 mL of DMF and added dropwise to a reaction solution cooled to 0°C over 5 minutes.
[0248] Once the dropwise addition was complete, the temperature was slowly raised to room temperature and stirred for 12 hours. Upon completion of the reaction, 400 mL of water was added dropwise, extracted twice with 350 mL of DCM, and then washed with 200 mL of saturated sodium chloride (NaCl) solution. 8 g of anhydrous magnesium sulfate (MgSO4) Compound 7 / DCM solution was obtained by adding and stirring, and filtering. DCM was distilled using a rotary evaporator, and silica gel chromatography was performed with ethyl acetate / hexane = 1 / 5 (v / v) solvent to obtain compound 7 (7.77 g, 80%).
[0249] Compound 7 : 1 HNMR (400MHz, CDCl3, δ): 6.34-6.36 (q, 2H), 4.33-4.38 (m, 1H), 4.26-4.29 (dd, 1H), 4.07-4.12 (q, 1H), 3.77-3.82 (m, 3H), 3.69-3.74 (m, 5H), 3.64-3.67 (t, 2H).
[0251] <Example 1.5> Synthesis of 2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethyl acetate {2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethyl acetate : Compound 8}
[0252] Under a nitrogen atmosphere, compound 7 (10 g, 35.87 mmol, 1 eq.) and potassium acetate (AcOK) (10.56 g, 0.11 mmol, 3 eq.) were added to 120 mL of dimethyl sulfoxide (DMSO) and reacted at 120 °C for 12 hours.
[0253] Once the reaction was complete, the solution was cooled to room temperature, 200 mL of water was added, and the mixture was extracted twice with 110 mL of DCM. The extracted DCM solution was washed with 120 mL of a saturated sodium chloride (NaCl) solution, 7 g of anhydrous magnesium sulfate (MgSO4) was added and stirred, and the solution was filtered to obtain a compound 8 / DCM solution. The DCM was distilled using a rotary evaporator, and silica gel chromatography was performed using an ethyl acetate / hexane = 1 / 4 (v / v) solvent to obtain compound 8 (9.50 g, 95%), which was 5.76 g of AcE2M-EDT.
[0254] Compound 8 : 1 HNMR (400MHz, CDCl3, δ): 6.34-6.36 (q. 2H), 4.32-4.37 (m, 1H), 4.23-4.29 (m, 3H), 4.06-4.11 (q, 1H), 3.77-3.81 (q, 1H), 3.67-3.73 (m, 7H), 2.10 (s, 3H).
[0256] <Example 1.6> Synthesis of 2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethanol {2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethanol : Compound 9}
[0257] Compound 8 (7 g, 25.11 mmol, 1 eq.) was added to 183.51 mL (200.88 mmol, 8 eq.) of 1 M aqueous sodium hydroxide (NaOH) solution and reacted at 60°C for 7 hours. After the reaction was complete, the solution was cooled to room temperature and neutralized to pH 7±0.2 by adding 35% hydrochloric acid (HCl) (16.72 g, 175.77 mmol, 7 eq.) dropwise, and extracted twice with 80 mL of DCM.
[0258] The extracted DCM solution was washed with 80 mL of saturated sodium chloride (NaCl) solution, 8 g of anhydrous magnesium sulfate (MgSO4) was added and stirred, and filtered to obtain a solution of Compound 9. The DCM was distilled using a rotary evaporator, and silica gel chromatography was performed using an ethyl acetate / hexane = 1 / 2 (v / v) solvent to obtain Compound 9 (5.43 g, 83%).
[0259] Compound 91 HNMR (400MHz, CDCl3, δ): 6.34-6.37 (q. 2H), 4.33-4.38 (m, 1H), 4.25-4.28 (dd, 1H), 4.07-4.12 (q, 1H), 3.69-3.81 (m, 8H), 3.62-3.64 (t, 2H).
[0261] <Example 1.7> Synthesis of Sodium 4-(2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethoxy)butane-1-sulfonate {Sodium 4-(2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethoxy)butane-1-sulfonate : Compound 10}
[0262] Under a nitrogen atmosphere, 60% sodium hydride (NaH) (1.30 g, 32.28 mmol, 1.2 eq.) was dispersed in 70 mL of anhydrous tetrahydrofuran (THF) and cooled to 0°C. Compound 9 (7 g, 26.90 mmol, 1 eq.) was dissolved in THF (30 mL) to prepare a compound 9 / THF solution, which was added dropwise to the NaH / THF solution at 0°C over 10 minutes. The reaction temperature was slowly increased from 0°C to 55–60°C and stirred for 2 hours, then cooled back to 0°C. 1,4-butanesultone (4.03 g, 29.60 mmol, 1.1 eq.) was dissolved in THF (20 mL), and this was slowly added dropwise over 10 minutes to a reaction solution cooled to 0°C, then the reaction temperature was slowly increased from 0°C to 55-60°C and stirred for 12 hours.
[0263] Upon completion of the reaction, the mixture was cooled to room temperature, anhydrous ethanol (EtOH, 30 mL) was added dropwise, and the mixture was stirred for 1 hour. Subsequently, THF and EtOH were distilled using a rotary evaporator, and anhydrous EtOH (350 mL) was added to dissolve the solution at room temperature. The solid compound that did not completely dissolve was removed by filtration through 0.45 µm PTFE, and the EtOH was distilled using a rotary evaporator to concentrate the reaction solution to 100 mL. 550 mL of diethyl ether was added dropwise to the concentrated reaction solution, and the mixture was stirred at room temperature for 2 hours. The precipitated solid was filtered under nitrogen pressure, washed with 10% (v / v) EtOH / Ether, and vacuum dried at 60°C for 12 hours to obtain compound 10 (4.27 g, 61).
[0264] Compound 10 : 1 HNMR (400MHz, CDCl3, δ): 6.57-6.60 (q. 2H), 4.30-4.32 (m, 1H), 4.23-4.26 (dd, 1H), 3.95-4.00 (q, 1H), 3.61-3.68 (q, 2H), 3.57-3.60 (m, 2H), 3.51-3.55 (m, 4H), 3.45-3.48 (m, 2H), 3.34-3.37 (m, 2H), 2.38-2.42 (t, 2H), 1.51-1.62 (m, 4H).
[0266] 2. Polymerization of the self-doping conductive polymer poly[4-(2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethoxy)butane-1-sulfonic acid], PSBE2M-EDT}
[0267] <Example 2> Polymerization of a conductive polymer applicable to organic light-emitting diodes and organic solar cells
[0268] A conductive polymer was polymerized using the Konradsson method as in Example 2.1 and the Okuzaki polymerization method as in Example 2.2, while adjusting the monomer concentration of compound 10 to 1 to 6 wt% according to the procedure briefly illustrated in Reaction Scheme 2, and purified by ion exchange resin, dialysis, and solidification as in Example 2.3.
[0269] [Reaction Equation 2]
[0270]
[0272] <Example 2.1> Synthesis of Poly{4-(2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethoxy)butane-1-sulfonate} : PSBE2M-EDT-Na} [Polymerization by Konradsson Method]
[0273] An aqueous solution was prepared by dissolving compound 10 (5 g, 19.20 mmol, 1 eq.) in 50 mL of water under a nitrogen atmosphere, and an FeCl3 / Na2S2O8 aqueous solution was prepared by dissolving ferric chloride (FeCl3) (1.93 g, 11.90 mmol, 0.62 eq.) and sodium persulfate (Na2S2O8) (9.14 g, 38.4 mmol, 2.0 eq.) in 55 mL of water.
[0274] Using a glass reactor (double jacket reactor), the aqueous solution of FeCl3 / Na2S2O8 was slowly added dropwise over 15 minutes while controlling the temperature of the aqueous solution of Compound 10 to 20–30°C. After the addition was complete, the mixture was stirred at 400 rpm for 3 hours at room temperature, and the polymerization reaction mixture was added dropwise to 1500 mL of acetone to precipitate as a solid. The precipitated solid was filtered under nitrogen pressure, washed with acetone, and vacuum dried at 60°C for 12 hours to obtain PSBE2M-EDT-Na (3.5 g, 70%).
[0276] <Example 2.2> Synthesis of Poly{4-(2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethoxy)butane-1-sulfonate} (Poly{sodium 4-(2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethoxy)butane-1-sulfonate : PSBE2M-EDT-Na} [Polymerization by Okuzaki Method]
[0277] An aqueous solution was prepared by dissolving compound 10 (5 g, 19.20 mmol, 1 eq.) in 45 mL of water under a nitrogen atmosphere, and then 95% sulfuric acid (H2SO4) (8.94 g, 139.2 mmol, 7.25 eq.) was added dropwise while cooling to room temperature. An aqueous solution of FeSO4-7H2O / (NH3)2S2O8 was prepared by dissolving ferrous sulfate heptahydrate (FeSO4-7H2O) (3.20 g, 11.52 mmol, 0.60 eq.) and ammonium persulfate ((NH3)2S2O8) (8.75 g, 38.4 mmol, 2.0 eq.) in 30 mL of water.
[0278] Using a glass reactor (double jacket reactor), an aqueous solution of FeSO4-7H2O / (NH3)2S2O8 was slowly added dropwise over 10 minutes while controlling the temperature of the polymerization reaction mixture to 20–30°C. After the addition was complete, the mixture was stirred at 400 rpm for 3 hours at room temperature, and the reaction mixture was added dropwise to 2500 mL of acetone to precipitate as a solid. The precipitated solid was filtered under nitrogen pressure, washed with acetone, and vacuum dried at 60°C for 8 hours to obtain PSBE2M-EDT-Na (3.85 g, 77%).
[0280] <Example 2.3> Synthesis of Poly{4-(2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethoxy)butane-1-sulfonic acid : PSBE2M-EDT} [Ion exchange, dialysis and solidification]
[0281] An aqueous solution of PSBE2M-EDT-Na (5 g) was prepared with water (150 ml), and 70 g of H-type cation exchange resin (Lewatit Monoplus S108H) was added and stirred at room temperature for 4 hours. Once ion exchange (Na→H) was completed, the ion exchange resin was filtered and washed with 200 ml of water to obtain an aqueous PSBM-EDT solution. Inorganic salts were removed by dialysis using a Spectra / Por 3 RC dialysis membrane (MWCO 3.5 kD) for about 5-7 days until the yellow color disappeared.
[0282] The dialyzed aqueous PSBM-EDT solution was concentrated by distilling water using a rotary evaporator until the reaction solution was 30 mL, and then 1500 mL of acetone was added dropwise to precipitate PSBM-EDT. The precipitated solid was filtered using nitrogen pressure, washed with acetone, and vacuum dried at 60°C for 12 hours to obtain PSBE2M-EDT (3 g, 60%) with a yield of 60%.
[0284] 3. Deep blue phosphorescence-sensitive superfluorescent organic electroluminescent device
[0285] <Example 3> Fabrication of a deep blue phosphorescence-sensitive superfluorescent organic electroluminescent device containing PSBE2M-EDT as a hole injection layer
[0286] The glass coated with ITO was treated with UV-ozone for 20 minutes to remove organic matter from the surface and make it hydrophobic. Poly[4-(2-(2-((2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)ethoxy)ethoxy)butane-1-sulfonic acid], PSBE2M-EDT, which is the hole injection layer (HIL), was thoroughly mixed, and a film was formed on the UV-ozone-treated ITO using a spin coating method, after which it was heated at 150°C for 20 minutes on a hot plate. A 15 nm thin film was formed by spin-coating PVK (0.5 wt%, cyclohexanone), which is a hole transport layer (HTL), at 2000 rpm.
[0287] Afterwards, load into a vacuum chamber and 1×10 -7 To deposit the emissive layer (EML) in a Torr vacuum, SiCzCz and SiTrzCz2 were applied as hosts, and thin films were formed using a co-deposition method with various compositions of Q(Bn)_Pt and t-Bu-v-DABNA as dopants. Subsequently, the first electron transport layer (ETL), mSiTrz (5 nm), and the second electron transport layer (ETL), TPBi (10 nm), were deposited in sequence. LiF, which is the electron injection layer (EIL), and aluminum, which is the second electrode, were deposited sequentially. To prevent contamination by organic materials, the deposition was carried out in a chamber separated from the organic material chamber.
[0289] The abbreviations of the compounds used in the fabrication of the deep blue phosphorescent superfluorescent organic electroluminescent device containing PSBE2M-EDT as the hole injection layer are summarized as shown in [Table 1] below.
[0291] abbreviation Full name (Korean / English) PVK Poly(9-vinylcarbazole) mSiTrz 2-Phenyl-4,6-bis(3-(triphenylsilyl)phenyl)-1,3,5-triazine TPBi 2,2,2"-(1,3,5-benzinetriyl)-tris(1-phenyl-1-H-benzimidazole) SiCzCz 9-(3-(triphenylsilyl)phenyl)-9H-3,9'-bicarbazole SiTrzCz2 9,9'-(6-(3-(triphenylsilyl)phenyl)-1,3,5-triazine-2,4-diyl)bis(9H-carbazole) t-Bu-ν-DABNA N7,N7,N13,N13,5,15-hexaphenyl-9,11-bis(4-(tert-butyl)phenyl)-5,9,11,15-tetrahydro-5,9,11,15-tetraaza-19b,20b-diboradinaphtho [3,2,1-de:1',2',3'-jk]pentacene-7,13-diamine Q(Bn)_Pt Platinum(II) 9-(4-(tert-butyl)pyridin-2-yl)-2-(3-(3-(quinolin-2-ylmethyl)-2,3-dihydro-1H-benzo[d]imidazol-1-yl)phenoxy)-9H-carbazole
[0293] <Experimental Example 1>
[0294] <Experimental Example 1.1> Experimental Method
[0295] 1 1H NMR spectra were recorded on a Bruker 400 MHz spectrometer in CDCl3 and DMSO-d6 using tetramethylsilane as an internal reference. Chemical shifts were for CDCl3 and DMSO-d6, respectively. 1 It was reported as a singlet at 7.26 and 2.54 ppm in 1H NMR.
[0296] UV-Vis and emission spectra were reported at room temperature using JASCO V-570 and Hitachi F-4500 fluorescence spectrophotometers. Transient signal photoluminescence (PL) measurements were performed at room temperature using a compact fluorescence lifetime spectrometer C11367. Thermal analysis was performed at 10°C / min under an N2 atmosphere. -1 It was performed with a Mettler Toledo TGA / SDTA 851e analyzer at a heating rate.
[0297] Cyclic voltammetry (CV) analysis was performed at 100 mV·s in anhydrous DCM solvent using 0.1 M TBAClO4 (Tetrabutylammonium Perchlorate) as the supporting electrolyte. -1 It was performed using a CHI 600C potentiostat (CH Instruments) at a scan rate. A platinum wire was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. The potential was referenced to the ferrocene / ferrocenium redox couple (Fc / Fc+).
[0298] Layer thickness was measured using an Alpha-step IQ surface profiler (KLA Tencor, San Jose, CA). Current density, voltage, and luminance characteristics were measured, and electroluminescence (EL) spectrum analysis was performed using a Keithley 2635A source meter and a CS2000 spectroradiometer (Konica Minolta).
[0299] External quantum efficiency (EQE), current efficiency (CE), and power efficiency (PE) values were determined using the M6100 electrical analysis system (McScience).
[0301] <Experimental Example 1.2> Experimental Results
[0302] FIGS. 2a to 2d show the voltage-current density-luminance, EL spectrum, luminance-external quantum efficiency, and luminance-current efficiency-power efficiency of a deep blue phosphorescence-sensitive superfluorescent organic electroluminescent device according to an embodiment of the present invention.
[0304] The organic electroluminescent device according to the present invention Referring to Figures 2a, 2b, 2c, and 2d, the turn-on voltage is 6.5 V, the maximum emission peak is 468 nm, and the color coordinates are (0.132, 0.126), indicating a deep blue color, and the maximum luminance is 6077 cd / m². 2 It can be seen that the maximum external quantum efficiency, current efficiency, and power efficiency are 4%, 4 cd / A, and 1.2 lm / W, respectively.
[0305] The results of the characteristic evaluation of the above organic electroluminescent device are shown in [Table 2] and [Table 3] below.
[0307] division Voltage(V) Luminance(cd / m 2 ) EL(nm) CIE(x,y) Turn-on At 1000 cd / m 2 Max. At 10 mA / m 2 At 10 mA / m 2 Device3 6.5 10.3 6077 468 (0.132, 0126)
[0309] division EQE(%) Current efficiency(cd / A) Power efficiency (Im / W) Max. At 1000 cd / m 2 Max. At 1000 cd / m 2 Max. At 1000 cd / m 2 Device3 4.0 3.9 4.0 3.9 1.2 1.1
[0312] 4. Fabrication of Organic Solar Cells
[0313] <Example 4> Fabrication of an organic solar cell containing PSBE2M-EDT as a hole transport layer
[0314] PSBE2M-EDT synthesized in Example 2.3 was introduced as a hole transport layer, and a photoelectric conversion layer material prepared by mixing PM6 and L8-BO in a weight ratio of 1:0.5 was dissolved in chlorobenzene solvent at a weight ratio of 1.5%. Subsequently, the material was spin-coated onto an ITO glass substrate incorporating the PSBE2M-EDT layer and heat-treated on a hot plate at 120°C for 10 minutes to introduce a photoelectric conversion layer with a thickness of 100 to 110 nm. PDINO was dissolved in methanol solvent at a weight ratio of 1.5% to form a thin film, and 110 o Heat treatment was performed at C for 10 minutes. Subsequently, 10 -7 A photovoltaic device was fabricated by thermally depositing aluminum to a thickness of 100 to 200 nm in a vacuum chamber with a vacuum level of less than torr. The fabricated photovoltaic device was heat-treated on a hot plate at 150 ℃ for 30 minutes in an argon atmosphere.
[0316] <Experimental Example 2> Evaluation of an organic solar cell containing PSBE2M-EDT as a hole transport layer
[0317] <Experimental Example 2.1> Experimental Method
[0318] In this experimental example, the electro-optical properties of the organic solar cell prepared in Example 4 above were measured.
[0319] Voltage-current density was measured under standard conditions (AM 1.5 (Air Mass 1.5 Global), 100 mW / cm², 25 ℃) using a Keithley 236 Source Measurement and a Solar Simulator (300W simulator models 81150 and 81250, Spectra-physics Co.) while irradiating with 100 mW / cm² of incident light through a solar photovoltaic simulation device.
[0321] <Experimental Example 2.2> Experimental Results
[0322] FIG. 3 is a graph of the current density-voltage (IV) characteristics measured for each organic solar cell device fabricated through Example 4 according to the present invention. Optical characteristics such as photo-short current, photo-open voltage, fill factor, and power conversion efficiency for the organic solar cell devices fabricated in Example 4 are shown in Table 4 below.
[0324] Optical short-circuit current (J SC )(mA / cm²) Optical open-circuit voltage (V OC )(V) Fill Factor * (FF) Power conversion efficiency ** (%) Example 4 14.2 0.84 0.58 7.0
[0325] * : Voltage value at maximum power point (V mp ) × Current density( I mp ) / (V oc × I sc )
[0326] ** : FF × { (I sc × V oc ) / Pin}, Pin = 100 [mW / cm²]
[0328] 5. Fabrication of thin films of multifunctional conductive polymers formed on various substrates
[0329] <Example 5> Fabrication of a thin film containing PSBE2M-EDT formed on a glass substrate
[0330] A solution for forming a thin film on a substrate was prepared by dissolving the PSBE2M-EDT synthesized in Example 2.3 at 1 wt% in a solvent of 30% water and 70% isopropyl alcohol and then dispersing the solution through a 0.45 micrometer filter. The solution was applied onto a 100 micrometer glass substrate, followed by coating using a bar coating machine. A film was then prepared by heat-treating the solution in a hot air circulating dryer at 120 degrees Celsius for 30 minutes to 1 hour for solvent removal and thermal annealing.
[0332] <Example 6> Fabrication of a thin film containing PSBE2M-EDT formed on a polyethylene terephthalate substrate
[0333] A thin film was formed by applying PSBE2M-EDT, a multifunctional conductive polymer synthesized in Examples 2.1, 2.2, and 2.3, respectively, onto a polyethylene terephthalate (PET) substrate. Subsequently, the substrate on which the thin film was formed was heat-treated for a certain period of time at 125±25℃ using a temperature-controlled hot plate. Afterward, the film was developed using water as the developer.
[0334] Separately, a thin film was formed by applying PSBE2M-EDT, a multifunctional conductive polymer synthesized in Examples 2.1, 2.2, and 2.3, respectively, onto a polyethylene terephthalate (PET) substrate, and then a laser beam was irradiated in the wavelength range of approximately 1 μm. At this time, a continuous wave laser was used as the laser equipment, with the output set to 8–10 W and the wavelength to 1064 nm, and the laser spot diameter set to 20–70 μm and the scanning speed set to 1,000 mm / sec for irradiation.
[0336] <Experimental Example 3> Evaluation of Thin Films of Multifunctional Conductive Polymers
[0337] <Experimental Example 3.1> Evaluation of Adhesion / Binding Strength Characteristics of Thin Film Containing PSBE2M-EDT Formed on a Polyethylene Terephthalate Substrate
[0338] When the thin film containing PSBE2M-EDT coated on the polyethylene terephthalate substrate of 5-2. above was developed, it was evaluated whether the thin film was stably bonded to the substrate without being washed away.
[0339] For reference, Fig. 5 is a photograph showing the adhesion / bonding strength of a thin film containing PSBE2M-EDT, a multifunctional conductive polymer derivative prepared according to Example 6 of the present invention.
[0342] Although a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced according to a preferred embodiment of the present invention, a method for manufacturing the same, and an organic electroluminescent device and an organic solar cell containing the same have been described as above, this is merely an example and those skilled in the art will understand that various changes and modifications are possible within the scope of the technical spirit of the present invention. Explanation of the symbols
[0344] 100 : Organic electroluminescent device 110: First electrode 120: Hole injection layer 130: Hole transport layer 140: Emitting layer 150: 1st electron transport layer 160: 2nd electron transport layer 170: Electron injection layer 180: Second electrode G: Bare Glass
Claims
Claim 1 Polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced, represented by the following chemical formula 1 [Chemical Formula 1] (wherein in the above Chemical Formula 1, R1 and R3 are each independently a straight-chain or branched-chain alkylene group having 1 to 10 carbon atoms, and R2 is an ethylene group, m is the number of repeating units of the ethylene oxide structure, which is 2, and n is the number of repeating units of the polythiophene main chain, which is an integer from 10 to 3,000. am.) Claim 2 A step of producing a thiophene-based sodium sulfonate salt-type precursor represented by the following chemical formula 6 using a thiophene-based compound represented by the following chemical formula 2; a step of reacting the thiophene-based sodium sulfonate salt-type precursor with 1,4-butanesultone to produce a thiophene-based sodium sulfonate salt-type monomer represented by the following chemical formula 7; a step of polymerizing the thiophene-based sodium sulfonate salt-type monomer to produce a polythiophene-based sodium sulfonate salt-type polymer represented by the following chemical formula 8; and a step of ion exchange of the polythiophene-based sodium sulfonate salt-type polymer Chemical formula 1a below A method for preparing a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced, comprising the step of producing a polythiophene-based conductive polymer derivative [Chemical Formula 2] [Chemical Formula 6] [Chemical Formula 7] [Chemical Formula 8] [Chemical Formula 1a] (However, the above Chemical formula 1a and in Chemical Formula 8, n is 10 to 3000.) Claim 3 A method for preparing a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent, wherein the step of producing the thiophene-based sodium sulfonate salt-type precursor comprises: a first step of producing a first intermediate represented by the following formula 4 using a thiophene-based compound represented by the formula 2 and a compound represented by the following formula 3; a second step of producing a second intermediate represented by the following formula 5 using the first intermediate; and a third step of producing a thiophene-based sodium sulfonate salt-type precursor represented by the formula 6 using the second intermediate. [Formula 3] [Formula 4] [Formula 5] Claim 4 In claim 2, the ion exchange is the Na of the sodium sulfonate functional group of the polythiophene-based sodium sulfonate salt-type polymer. + ul H + A method for preparing a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced, characterized by changing to a sulfonic acid functional group through ion exchange. Claim 5 In Article 2, The above A method for preparing a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent, characterized by sequentially performing dialysis and coagulation processes after ion exchange. Claim 6 A first electrode; a second electrode formed opposite to the first electrode; and one or more organic layers disposed between the first electrode and the second electrode, wherein one or more of the organic layers are as follows Organic electroluminescent device characterized by comprising a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced as Chemical Formula 1 [Chemical Formula 1] (wherein in the above Chemical Formula 1, R1 and R3 are each independently a straight-chain or branched-chain alkylene group having 1 to 10 carbon atoms, and R2 is an ethylene group, m is the number of repeating units of the ethylene oxide structure, which is 2, and n is the number of repeating units of the polythiophene main chain, an integer from 10 to 3,000 am.) Claim 7 An organic electroluminescent device according to claim 6, wherein the organic layer comprises one or more selected from a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer, or a mixed layer thereof. Claim 8 In claim 7, the hole injection layer is as follows: Organic electroluminescent device characterized by comprising a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced as Chemical Formula 1a [Chemical Formula 1a] (However, in the above chemical formula 1a, n is 10 to 3000.) Claim 9 An organic electroluminescent device according to claim 7, wherein the light-emitting layer is characterized by being deposited by a co-deposition method of a host and a dopant. Claim 10 In claim 6, the organic electroluminescent device is characterized by emitting a deep blue light. Claim 11 A first electrode; a second electrode formed opposite to the first electrode; and one or more organic layers disposed between the first electrode and the second electrode, wherein one or more of the organic layers are as follows Organic solar cell characterized by comprising a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced as Chemical Formula 1 [Chemical Formula 1] (wherein in the above Chemical Formula 1, R1 and R3 are each independently a straight-chain or branched-chain alkylene group having 1 to 10 carbon atoms, and R2 is an ethylene group, m is the number of repeating units of the ethylene oxide structure, which is 2, and n is the number of repeating units of the polythiophene main chain, an integer from 10 to 3,000 am.) Claim 12 An organic solar cell according to claim 11, wherein the organic layer comprises one or more selected from a hole transport layer, a photoactive layer, an electron transport layer, or a mixture thereof, and the hole transport layer comprises a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced as shown in the following chemical formula 1a [Chemical Formula 1a] (However, in the above chemical formula 1a, n is 10 to 3000.) Claim 13 An organic solar cell according to claim 12, wherein the photoactive layer is composed of a bulkhetero junction (BHJ) in which a non-fullerene electron donor and a fullerene electron acceptor are stacked in a mixed phase. Claim 14 In claim 12, the electron transport layer is, N,N'-Bis(N,N-Dimethylpropane-1-amine oxide)perylene-3,4,9,10-tetracarboxylic diimide An organic solar cell characterized by comprising (N,N'-Bis(N,N-dimethylpropan-1-amine oxide)perylene-3,4,9,10-tetracarboxylic diimide, PDINO) Claim 15 A method for manufacturing an organic electronic device, characterized by comprising the steps of: forming an anode on a substrate; forming an organic layer containing the compound of claim 1 on the anode; and forming a cathode on the organic layer. Claim 16 A method for manufacturing an organic electronic device according to claim 15, wherein the organic electronic device is an organic electroluminescent device, and the organic layer comprises a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, and an electron injection layer, and wherein the hole injection layer, the hole transport layer, the light-emitting layer, the electron transport layer, and the electron injection layer are sequentially stacked and formed on the anode. Claim 17 A method for manufacturing an organic electronic device according to claim 15, wherein the organic electronic device is an organic solar cell, the organic layer comprises a hole transport layer, a photoactive layer, and an electron transport layer, and the hole transport layer, the photoactive layer, and the electron transport layer are sequentially stacked and formed on the anode. Claim 18 In Clause 16, the above-mentioned hole injection layer is as follows: Method for manufacturing an organic electronic device characterized by comprising a polythiophene-based conductive polymer derivative having an ethylene oxide sulfonic acid side chain substituent introduced as Chemical Formula 1a [Chemical Formula 1a] (However, the above chemical formula 1 a In this case, n is 10 to 3000. Claim 19 A method for manufacturing an organic electronic device according to claim 15, wherein the step of forming an organic layer containing the compound of claim 1 on the anode further comprises the step of irradiating a laser beam or performing heat treatment after stacking the organic layer containing the compound of claim 1 on the anode. Claim 20 A method for manufacturing an organic electronic device according to claim 15, wherein the step of forming an organic layer containing the compound of claim 1 on the anode further comprises: a step of irradiating a laser beam or performing heat treatment after depositing the organic layer containing the compound of claim 1 on the anode; and a step of developing using water as a developer.
Citation Information
Patent Citations
Process for preparing an aqueous or non-aqueous solution or dispersion of a polythiophene or thiophene copolymer
KR100936426B1
Process for preparing an aqueous or non-aqueoussolution or dispersion of a polythiophene or thiophenecopolymer
KR1020050044681A
Highly transparent electrochromic coating material, method for producing the same and use of the material
KR1020090087942A
Method for preparing mesoporous conducting polymers
KR1020110050918A
Composition comprising pedot / PSS and fluorinated polymers and transparent electrode film using same
KR1020150030841A